95.5k views
5 votes
What is the answer to this question ?

What is the answer to this question ?-example-1
User Leremjs
by
5.9k points

1 Answer

6 votes

Answer:

third option

Explanation:

Given x = a and x = b are zeros of f(x), then

(x - a) and (x - b) are factors of f(x) and f(x) is the product of the factors

f(x) = (x - a)(x - b)

Given the zeros are x = - 3, x = 0 and x = 4 , then

(x - (- 3) ), (x - 0), (x - 4) are factors, that is

(x + 3), x, (x - 4) , so

f(x) = x(x + 3)(x - 4)

User Yoann Kergall
by
5.7k points